A cross-sectional study on foot loading patterns in elite soccer players of different ages - Hotfiel, Thilo; Golditz, Tobias; Wegner, Jessy; Pauser, Johannes; Brem, Matthias; Swoboda, Bernd; Carl, Hans-Dieter (Journal of Back and Musculoskeletal Rehabilitation, 2020)
BACKGROUND: Alterations in plantar loading patterns are risk factors for stress injuries of the lower limb, particularly of the foot and ankle. Epidemiological studies have revealed a higher incidence of soccer-related stress fractures of the fifth metatarsal (MT V) in younger athletes than in their adult counterparts. OBJECTIVE: The aim of the present study was to assess the plantar pressure distributions of members of four high-level soccer teams of different age groups to identify age-related differences in loading patterns. METHODS: A total of 65 elite soccer players were included in the study. Data were computed with sensor-loaded insoles (pedar® X system, novel Inc., Munich, Germany) while the players ran in soccer shoes. Plantar pressures for nine defined regions on the preferred and nonpreferred foot were analyzed. RESULTS: The participants consisted of 17 elite male soccer professionals from the first national league (mean 23 years, height 184 cm, weight 81 kg), 14 players from the under-21 squad (U21, 20 years, 180 cm, 75 kg), 15 players from the U17 squad (16 years, 176 cm, 69 kg) and 19 players from the U16 squad (15 years, 179 cm, 70 kg). We detected statistically significantly elevated peak pressures on the lateral aspects of the nonpreferred foot compared with the preferred foot in the U16 and U17 players, corresponding to a relative increase by 29% (p= 0.044) in the lateral midfoot, a relative increase by 24% (p= 0.031) in MT heads 4-5 in the U16 players and a difference of 18% (p= 0.049) in the lateral midfoot in the U17 players. In contrast, the U21 and adult professional players displayed symmetric plantar pressure distributions in all foot regions. CONCLUSIONS: In contrast to adult elite soccer players, adolescents demonstrate asymmetric foot loading patterns with increased peak loads in the lateral aspects of the nonpreferred foot. Our results may provide some explanation for MT V stress fractures that occur in elite adolescents.
CRIS-Team Scopus Importer:2020-12-11
Keywords: fifth metatarsal; foot injury; overuse injuries; pedobarography; soccer; Sports injuries; stress fractures; stress reaction

Early repolarization, left ventricular diastolic function, and left atrial size in professional soccer players - Wilhelm, Matthias; Brem, Matthias; Rost, Christian; Klinghammer, Lutz; Hennig, Friedrich; Daniel, Werner; Flachskampf, Frank (American Journal of Cardiology, 2010)
Recent data have suggested a relation among long-term endurance sport practice, left atrial remodeling, and atrial fibrillation. We investigated the influence of an increased vagal tone, represented by the early repolarization (ER) pattern, on diastolic function and left atrial size in professional soccer players. Fifty-four consecutive athletes underwent electrocardiography, echocardiography, and exercise testing as part of their preparticipation screening. Athletes were divided into 2 groups according to presence or absence of an ER pattern, defined as a ST-segment elevation at the J-point (STE) <0.1 mm in 2 leads. For linear comparisons average STE was calculated. Mean age was 24 ± 4 years. Twenty-five athletes (46%) showed an ER pattern. Athletes with an ER pattern had a significant lower heart rate (54 ± 9 vs 62 ± 11 beats/min, p = 0.024), an increased E/e′ ratio (6.1 ± 1.2 vs 5.1 ± 1.0, p = 0.002), and larger volumes of the left atrium (25.6 ± 7.3 vs 21.8 ± 5.0 ml/m2, p = 0.031) compared to athletes without an ER pattern. There were no significant differences concerning maximum workload, left ventricular dimensions, and systolic function. Univariate regression analysis revealed significant correlations among age, STE, and left atrial volume. In a stepwise multivariate regression analysis age, STE and e′ contributed independently to left atrial size (r = 0.659, p <0.001). In conclusion, athletes with an ER pattern had an increased E/e′ ratio, reflecting a higher left atrial filling pressure, contributing to left atrial remodeling over time. © 2010 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10

SARS-CoV-2 transmission during an indoor professional sporting event - Pauser, Johannes; Schwarz, Chantal; Morgan, James; Jantsch, Jonathan; Brem, Matthias (Scientific Reports, 2021)
Sporting events with spectators can present a risk during the COVID-19 pandemic of becoming potential superspreader events that can result in mass-infection amongst participants-both sportspeople and spectators alike. In order to prevent disease transmission, many professional sporting bodies have implemented detailed hygiene regulations. This report analyzes SARS-CoV-2 transmission during a professional sports event (2nd division professional basketball in Germany). Whilst social distancing in this context is not always possible, the rate of infection was significantly reduced by wearing face masks that cover the mouth and nose. There was no infection amongst individuals who continuously wore medical particle filter masks (Category KN95/FFP2 or higher) during this sporting event.
CRIS-Team WoS Importer:2021-11-05